Giant posterior gastric perforation in a 40 years old male: a case report - Naqvi, Raheel Hussan; Singh, Khushwant; Singh, Rahul (International Surgery Journal, 2021)
Posterior perforation of gastric ulcer is a rare clinical entity and has a propensity for delayed presentation and missed diagnosis. By virtue of their location, posterior gastric perforations may rupture into the retroperitoneum which leads to abscess formation and development of adhesions and consequently, leads to a delay in the onset of symptoms. Alternatively, ulcers located in the fundus or the body of the stomach may perforate into the lesser sac, which results in sealing off the perforation and less dramatic clinical signs and symptoms. This delay in presentation contributes to higher morbidity, higher infection rates and higher mortality. Thus, it is essential to have a high index of suspicion for this condition, particularly in patients with a protracted clinical presentation and classical risk factors so that timely, life-saving intervention is possible. We report a case of giant posterior gastric perforation with benign histopathology in a 40-years-old male. This case is being presented due to the rarity of this clinical entity and the relative paucity of literature on the same.